Pharmacological and non-pharmacological prevention and management of delirium in critically ill and palliative patients in the inpatient setting: a review - Chan, Leah; Corso, German (Frontiers in Medicine, 2024)
Introduction This review explores delirium in critically ill patients in the inpatient setting, focusing on its prevention and management. It evaluates the efficacy of both current pharmacological and non-pharmacological interventions, aiming to provide a comprehensive overview. Methods A systematic literature search was conducted to identify relevant studies investigating the prevention and management of delirium resulting in a final sample of 26 articles for analysis. Results Of the 26 articles analyzed for this review (N = 8,831 participants) of controlled trials, 16 studies examined the prevention of delirium, 9 explored the treatment of delirium, and 1 investigated both prevention and treatment of delirium. Discussion Among the reviewed studies, there is evidence that non-pharmacologic methods are effective in the prevention of delirium. Evidence regarding pharmacological interventions for delirium prevention is varied and inconclusive, with some indication that atypical antipsychotics like aripiprazole and quetiapine may reduce the incidence of delirium. Regarding the treatment of delirium, there is limited evidence supporting the use of pharmacological agents. Additional double-blinded, randomized, placebo-controlled clinical trials are needed to investigate the efficacy of pharmacologic agents for diverse hospitalized populations.